2023
DOI: 10.3390/biomedicines11082219
|View full text |Cite
|
Sign up to set email alerts
|

A Single Application of Cerebellar Transcranial Direct Current Stimulation Fails to Enhance Motor Skill Acquisition in Parkinson’s Disease: A Pilot Study

Abstract: Parkinson’s disease (PD) is a progressive neurodegenerative disorder that leads to numerous impairments in motor function that compromise the ability to perform activities of daily living. Practical and effective adjunct therapies are needed to complement current treatment approaches in PD. Transcranial direct current stimulation applied to the cerebellum (c-tDCS) can increase motor skill in young and older adults. Because the cerebellum is involved in PD pathology, c-tDCS application during motor practice cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 73 publications
(173 reference statements)
0
5
0
Order By: Relevance
“…These findings suggest that comprehending the neural correlates and molecular mechanisms underlying anxiety disorders, particularly in the context of fear acquisition and extinction, opens new avenues for therapeutic interventions. Moreover, the combination of neuropharmacological adjuvants, such as NMDA agonists and cannabinoids, with noninvasive brain stimulation techniques, such as transcranial magnetic stimulation and transcranial direct current stimulation, offers a promising approach to enhance the effectiveness of existing treatments [ 32 , 33 , 34 , 35 , 36 , 37 ]. Overall, these articles emphasize the complexity and multifaceted nature of memory and learning processes as well as the significance of understanding the neural correlates and molecular mechanisms underlying these phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that comprehending the neural correlates and molecular mechanisms underlying anxiety disorders, particularly in the context of fear acquisition and extinction, opens new avenues for therapeutic interventions. Moreover, the combination of neuropharmacological adjuvants, such as NMDA agonists and cannabinoids, with noninvasive brain stimulation techniques, such as transcranial magnetic stimulation and transcranial direct current stimulation, offers a promising approach to enhance the effectiveness of existing treatments [ 32 , 33 , 34 , 35 , 36 , 37 ]. Overall, these articles emphasize the complexity and multifaceted nature of memory and learning processes as well as the significance of understanding the neural correlates and molecular mechanisms underlying these phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…Integrating these interdisciplinary approaches further adds impetus and optimizes strategies, including drug development research, leading to the testing and assessment of potential lead compounds. These outcomes enable researchers to evaluate the effects of novel interventional approaches such as drug-assisted brain stimulation [ 106 , 209 , 210 , 211 , 212 , 213 , 214 ]. These methods demonstrate promise for the development of new and more effective treatments, including novel drugs [ 215 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings of this study could have significant implications for the management of patients with epilepsy, particularly those who are candidates for surgery. de Albuquerque et al investigated the effect of a single application of cerebellar transcranial direct current stimulation (c-tDCS) on motor skill acquisition in PD [ 53 ]. The pilot study found that a single application of c-tDCS failed to enhance motor skill acquisition in the condition.…”
Section: Special Issue Articlesmentioning
confidence: 99%